Proteomic and metabolomic investigation of serum lactate dehydrogenase elevation in COVID‐19 patients. Issue 15 (28th May 2021) - Yan, Haixi; Liang, Xiao; Du, Juping; He, Zebao; Wang, Yu; Lyu, Mengge; Yue, Liang; Zhang, Fangfei; Xue, Zhangzhi; Xu, Luang; Ruan, Guan; Li, Jun; et al.
Abstract: Serum lactate dehydrogenase (LDH) has been established as a prognostic indicator given its differential expression in COVID‐19 patients. However, the molecular mechanisms underneath remain poorly understood. In this study, 144 COVID‐19 patients were enrolled to monitor the clinical and laboratory parameters over 3 weeks. Serum LDH was shown elevated in the COVID‐19 patients on admission and declined throughout disease course, and its ability to classify patient severity outperformed other biochemical indicators. A threshold of 247 U/L serum LDH on admission was determined for severity prognosis. Next, we classified a subset of 14 patients into high‐ and low‐risk groups based on serum LDH expression and compared their quantitative serum proteomic and metabolomic differences. The results showed that COVID‐19 patients with high serum LDH exhibited differentially expressed blood coagulation and immune responses including acute inflammatory responses, platelet degranulation, complement cascade, as well as multiple different metabolic responses including lipid metabolism, protein ubiquitination and pyruvate fermentation. Specifically, activation of hypoxia responses was highlighted in patients with high LDH expressions. Taken together, our data showed that serum LDH levels are associated with COVID‐19 severity, and that elevated serum LDH might be consequences of hypoxia and tissue injuries induced by inflammation.